The Principles and Types of Equivalent Forms of Declension in the Noun System of Modern Literary Eastern Armenian - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2023)
In the course of the development of the language in the vocative system of modern literary Eastern Armenian, new vocative variants are formed and developed, bringing forth vocative dualities. The reasons for their occurrence are the scope of the dominance of the ի (i) case, the interpenetrations of the traditionally transmitted equivalent forms of declension, the underlying declensions, and the development of non-phonetic based formations, and the parallel use of forms on a semantic and functional-stylistic basis. On this basis, the varieties of vocative equivalent forms are classified as follows: 1. Equivalent forms of declension - according to the composition of the singular genitive case, which is conditioned by the expansion of the ի (i) equivalent form (սյան/սյունի, այգու/այգիի, սկեսրոջ/սկեսուրի, ծննդյան/ծննդի), 2. Conjugations of equivalent forms - oblique conjugations with different endings (կղզուց/կղզիից, շարժմամբ/շարժումով, երջանկությամբ/երջանկությունով), 3. Basic equivalent forms - oblique inflections with the same ending but with different basic equivalent forms (մարզիչի/մարզչի, օրից/օրվանից, գրչով/գրիչով, օրով/օրվանով, Լոռիում/Լոռում), 4. Semantic equivalent forms – they are conditioned by different meanings of the word (օրի/օրվա, տարու/տարիի, ժամից/ժամվանից, գիշերով/գիշերվանով), 5. Stylistic equivalent forms – they are with different stylistic-expressive meanings (սգո/սգի, դստեր/դուստրի, Լոռվա/Լոռու). Those are thoroughly discussed and described in the article. The formation and use of case equivalent forms is a continuous grammatical process. This part of the Armenian morphological system, parallel with the verb conjugation system, makes it perhaps the richest field of Armenian grammar.